A Cognitive Stylistic Study of Trauma Representation and Dystopian Reality Construction in The Hunger Games: A Functional Analysis of Metaphors and Similes - Triyana Sari; Rayhan Izzati Basith (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study examines how metaphors and similes in Suzanne Collins’s The Hunger Games represent the protagonist’s trauma and construct the dystopian reality of Panem and the Capitol. Although previous studies have discussed dystopian themes and figurative language in the novel, limited attention has been paid to how these expressions work from a cognitive stylistic perspective to shape readers’ understanding of trauma and social injustice. Using a descriptive qualitative approach, this study analyzes selected figurative expressions and narrative passages from Katniss’s narration and from descriptions of Panem and the Capitol through textual analysis grounded in conceptual metaphor theory and cognitive stylistics. The findings show that figurative expressions related to bodily pain, fear, and entrapment portray trauma as an embodied psychological burden, while similes emphasizing the Capitol’s spectacle and excess reinforce unequal power relations and the normalization of violence. These patterns deepen readers’ engagement with Katniss’s experience and reveal mechanisms of domination and resistance within the dystopian order. Overall, the study demonstrates that figurative language functions not only as an aesthetic device but also as a cognitive means of linking personal suffering to broader sociopolitical critique.